2020
DOI: 10.1017/ice.2020.1346
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the accuracy of administrative data for the detection of surgical site infections

Abstract: We performed a retrospective analysis of the changes in accuracy of International Classification of Diseases, Clinical Modification (ICD-CM) diagnosis codes for colectomy and hysterectomy surgical site infection surveillance. After the transition from ICD-CM ninth edition to tenth edition codes, there was no significant change in the accuracy of these codes for SSI surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…One study showed no significant change in the performance of SSI surveillance codes for colon surgery and abdominal hysterectomy after the transition to ICD-10. 25 We previously published a comparison of the ICD-9 diagnosis codes to ICD-10 diagnosis codes (Supplementary Appendix Table 3 online). 19 In summary, our findings provide strong support for the current methodology being used by CMS and some state health departments to identify records to review during validation site visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed no significant change in the performance of SSI surveillance codes for colon surgery and abdominal hysterectomy after the transition to ICD-10. 25 We previously published a comparison of the ICD-9 diagnosis codes to ICD-10 diagnosis codes (Supplementary Appendix Table 3 online). 19 In summary, our findings provide strong support for the current methodology being used by CMS and some state health departments to identify records to review during validation site visits.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed no significant change in the performance of SSI surveillance codes for colon surgery and abdominal hysterectomy after the transition to ICD-10. 25 We previously published a comparison of the ICD-9 diagnosis codes to ICD-10 diagnosis codes (Supplementary Appendix Table online). 19…”
Section: Discussionmentioning
confidence: 99%